Impact of atmospheric deposition on the contrasting iron biogeochemistry of the North and South Atlantic Ocean. Issue 4 (13th November 2013) - Ussher, Simon J.; Achterberg, Eric P.; Powell, Claire; Baker, Alex R.; Jickells, Tim D.; Torres, Ricardo; Worsfold, Paul J.
<x xml:space="preserve">Abstract</x> [1] Dissolved iron (dFe) distributions and atmospheric and vertical subduction fluxes of dFe were determined in the upper water column for two meridional transects of the Atlantic Ocean. The data demonstrate the disparity between the iron biogeochemistry of the North and South Atlantic Ocean and show well‐defined gradients of size fractionated iron species in surface waters between geographic provinces. The highest dFe and lowest mixed layer residence times (0.4–2.5 years) were found in the northern tropical and subtropical regions. In contrast, the South Atlantic Gyre had lower dFe concentrations (<0.4 nM) and much longer residence times (>5 years), presumably due to lower atmospheric inputs and more efficient biological recycling of iron in this region. Vertical input fluxes of dFe to surface waters ranged from 20 to 170 nmol m–2 d–1 in the North Atlantic and tropical provinces, whereas average fluxes of 6–13 nmol m–2 d–1 were estimated for the South Atlantic. Our estimates showed that the variable dFe distribution over the surface Atlantic (<0.1–2.0 nM) predominantly reflected atmospheric Fe deposition fluxes (>50% of total vertical Fe flux to surface waters) rather than upwelling or vertical mixing. This demonstrates the strength of the connection between land‐derived atmospheric Fe fluxes and the biological cycling of carbon and nitrogen in the Atlantic Ocean.